Inside Front Cover: Design of polymers for siRNA delivery: Recent progress and challenges (View 3/2021). Issue 3 (17th June 2021) - Wang, Hui; Zhang, Song; Lv, Jia; Cheng, Yiyun
Abstract : RNAi‐mediated gene therapy is gradually becoming a conventional approach for the treatment of various diseases. One of the major challenges for clinical translation of RNAi is to efficiently deliver siRNA into targeted tissues and cells. Herein, in article number 20200026 Yiyun Cheng, Jia Lv and their co‐workers have reviewed recent advances in the design of functional polymers to overcome the multiple extracellular and intracellular barriers during siRNA delivery in vitro and in vivo, and provided perspectives for future siRNA delivery systems.